ANALISIS PENGGUNAAN OBAT HERBAL PASIEN DIABETES MELLITUS TIPE II DI KOTA LANGSA - Diza Fathamira Hamzah (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
Diabetes mellitus is one of degenerative disease which is relatively high in Langsa City. Nowadays, the usage of herbal medicines for diabetics  is highly recommended to reduce the side effects of the usage of antidiabetic drugs,  which is consumed for  a long period time. This research aims to analyze the usage of herbal medicines in Diabetics with type II Diabetes Mellitus. The population in this study were 3647 people and 97 of them were sample. The sampling technique was cluster random sampling. The results showed that the majority of DM patients were women (50.5%) with work as housewives (30.9%). The most herbal medicine used was turmeric (39.2%) with motivation to use are cheap and easily to get  (40.2%). It is suggested to Langsa city government to develop a family medicinal program as well as increase the health promotion efforts of the usage herbal drugs in order to reduce the side effects of the usage of antidiabetic drugs.